La Cultura Maker y el desarrollo del pensamiento crítico en el sexto grado de Educación General Básica - Poma Cuenca, Nathaly Camila (2023)
The work entitled: The Maker Culture and the development of critical thinking in the sixth grade of General Basic Education, has as general objective: To determine the impact of the Maker Culture in the development of critical thinking in the sixth grade of General Basic Education; this research has a mixed approach, it is descriptive, quasi-experimental design since we worked with a homogeneous group performing the application of a pre-test and post-test after having applied the Maker-Educa proposal; we made use of the following methods: scientific, statistical, analytical, synthetic and descriptive: scientific, statistical, analytical, synthetic and descriptive methods were used, which contributed to elucidate the work of curricular integration, to give foundation to the different postulates of the authors and, based on them, to infer criteria with the purpose of approaching the proposed topic; the information was collected through the application of a test called Watson Glaser's Critical Thinking Test and a structured interview; The population consisted of one teacher and twenty-two students; the results show the need to undertake improvement actions to develop critical thinking, for which the alternative proposal called Maker-Educa was planned and successfully executed through a didactic guide with various activities based on the Maker Culture, concluding that it contributes to the development of critical thinking in students.